A novel behavioural approach to assess responsiveness to auditory and visual stimuli before cognitive testing in family dogs - Bognár, Zsófia; Piotti, Patrizia; Szabó, Dóra; Le Nézet, Louis; Kubinyi, Enikő (Applied animal behaviour science, 2020)
•Non-invasive check of the sensory capacities of ageing dogs before enrolling them in cognitive tests is suggested.•Responsiveness to visual stimuli can be tested based on the distance of the stimuli from the dog.•Lighting conditions of the testing room also influence visual responsiveness.•Dogs’ reactivity to auditory stimuli was lower in older dogs.•Owners’ evaluation of their dogs’ vision and hearing positively correlated with the test performance. Visual and auditory impairments can have a large impact on performance in cognitive tests. It is important to evaluate the sensory capacities of dogs before enrolling them in cognitive tests, in order to exclude sensory impairment as confounding effect. Therefore we designed multiple non-invasive testing paradigms to detect subjects with potential auditory and visual impairment, without requiring extensive training for the dog. Multiple testing was a means to add internal reliability, and to reduce the risk of false positives due to habituation and previous learning or false negatives due to random errors. Our sensory test battery consisted of four subtests: (1) ‘Clapping’ auditory test, (2) ‘Recorded sound’ auditory test, (3) ‘Distance’ visual test, and (4) ‘Darkness’ visual test. The 'Clapping test' was similar to the clapping test used by veterinarians, with the addition that the clapping was performed at various distances from the dog. In the ‘Recorded sound test’, the dogs' reaction to various sounds played back at different volumes. In the ‘Distance test’ we placed a small piece of food on one of four plates placed on the grounds at varying distances from the dogs. In the 'Darkness test’, we measured the dogs' performance in walking through an S-shaped route during artificial dusk and daylight-like conditions. We were able to design two standardised tests measuring dogs’ responsiveness to visual stimuli and its variance based on a) the distance of stimuli from the dog, and b) the lighting conditions in the room. The performance in our tests requires two elements of the visual function, namely visual acuity and vision in dusk. These tests should be considered for further validation, in order to evaluate their usefulness as screening tools for the decline in dogs’ visual function. In our behaviour tests measuring the response to auditory stimuli, we found that dogs reacted similarly to different sounds. However, older dogs reacted less frequently to sounds with lower decibel, suggesting that older dogs become less reactive to auditory stimuli. The tests we developed are useful to identify subjects who do show a behavioural reaction to the stimuli typically used in cognitive tests (rewards, small objects, barriers, etc.) under various levels of artificial light. It is possible to identify the dogs’ baseline level of reactivity to visual/auditory stimuli before these are used in cognitive tests.